2021
DOI: 10.1101/2021.01.12.20248726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in the Health of Adolescent Athletes: A Comparison of Health Measures Collected Before and During the CoVID-19 Pandemic

Abstract: ContextIn the spring of 2020, schools closed to in-person teaching and sports were cancelled to control the transmission of CoVID-19. The changes that took place to the physical and mental health among young athletes during this time remain unknown, however.ObjectiveIdentify changes in the health (mental health, physical activity and quality of life) of athletes that occurred during the CoVID-19 pandemic.DesignCross sectional study.SettingSample recruited via social media.Patients or Other Participants3243 Wis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…This seems to suggest that while PLY athletes continue to demonstrate slightly higher levels of depression and anxiety than historical values, the mental health burden among DNP athletes is considerably worse. 7 In fact, the DNP group demonstrates levels of moderate to severe anxiety and depression symptoms similar to those identified in a nationwide sample for adolescent athletes in May 2020 (anxiety = 36.7%, depression = 27.1%). 7 Given the adolescent mental health crisis that existed prior to the onset of COVID-19, and the known mental health benefits of sport participation, this data seems to suggest that adolescent athletes who are unable to return to sports may be at a significantly greater risk for mental health issues.…”
Section: Mental Healthmentioning
confidence: 54%
See 2 more Smart Citations
“…This seems to suggest that while PLY athletes continue to demonstrate slightly higher levels of depression and anxiety than historical values, the mental health burden among DNP athletes is considerably worse. 7 In fact, the DNP group demonstrates levels of moderate to severe anxiety and depression symptoms similar to those identified in a nationwide sample for adolescent athletes in May 2020 (anxiety = 36.7%, depression = 27.1%). 7 Given the adolescent mental health crisis that existed prior to the onset of COVID-19, and the known mental health benefits of sport participation, this data seems to suggest that adolescent athletes who are unable to return to sports may be at a significantly greater risk for mental health issues.…”
Section: Mental Healthmentioning
confidence: 54%
“…This study builds on prior research demonstrating the dramatic changes in physical and mental health following the cancellation of high school sports in the spring of 2020. 6,7 A limitation of the prior studies is the difficulty discerning if the health changes reported were primarily due to the restrictions on sport participation or the result of other factors such as sex, age, socioeconomic status, or the lack of in-person school attendance. After controlling for grade, sex, school instructional delivery method and the % of students qualifying for free and reduced lunch, our findings demonstrate that athletes who did not play interscholastic sports experienced significantly worse symptoms of anxiety and depression, lower levels of physical activity and worse HRQoL compared to athletes who did not play sports in fall 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young adults in other countries are also experiencing the greatest levels of mental distress during this pandemic [3,4]. Adolescents in the US [5,6] and in other countries [7e9] have also experienced deteriorations in mental health, happiness, and life satisfaction.…”
mentioning
confidence: 99%
“…4,5 Prior research has demonstrated an increase in symptoms of depression and anxiety in adolescents related to quarantines and lock down orders, 6,7 and it has been suggested that youth athletes may have been particularly negatively affected by the cancelation of school and sports. 8 Physical activity levels in youth athletes have also been affected by the cancelation of youth sports. Recent studies have demonstrated a decrease in physical activity among youth during the pandemic.…”
Section: Introductionmentioning
confidence: 99%